PERENCANAAN RUMAH TAHFIDZPRENEUR DI DESA CIBADAK, CARIU, BOGOR, JAWA BARAT, INDONESIA - Lissimia, Finta; Maghfurah, Fadwah; Surury, Isti'anah; Sobri, Adna; Syahputra, Haikal Bintang; Alnawawi, Muhammad Sidiq; Saputra, Dymas; Yusuf, Mohammad (ABDI MAKARTI, 2024)
Rumah Tahfidzpreneur Annur in Cibadak Village, Cariu, Bogor, West Java requires assistance in the planning process. This community service is motivated by the society's intention to build a tahfidz facility on land of approximately 5,200 m2 in Cibadak Village, Cariu, Bogor. The land is located in a residential area that is ideal for building a Tahfidz House. Rumah Tahfidzpreneur Annur will be built with guesthouse dormitory facilities, owner's house, farm, prayer room, multipurpose room, library, informal class, cooperative, and management office. The design recommendation is to divide these spaces into public, semi-public, private, and service areas. The main access is on the main road side, the public area is adjacent to this side. The private area is on the back side to ensure privacy. The service area is also on the back side. The middle part is filled with a semi-public area. The distant water source creates obstacles to water distribution and it is recommended to install a centrifugal pump so that water distribution is smooth. The results of physical and chemical tests on the water on the Rumah Tahfidzpreneur Annur land show that the water meets household standards but it is necessary to install a filter in the water reservoir so that the water is free of bacteria. Keywords: Rumah Tahfidzpreneur Annur, site concept, water distribution, clean water filter